Use the properties of operations and rules for multiplying and dividing to solve: (-3/5)x(5/16)x(7/12)divided by (-3/16)x(-5/7)

3 answers

To solve this expression, we will use the properties of operations for dividing and multiplying fractions.

First, we can simplify each multiplication separately:
(-3/5) x (5/16) x (7/12) = (-3 x 5 x 7) / (5 x 16 x 12) = -105 / 960

(-3/16) x (-5/7) = (3 x 5) / (16 x 7) = 15 / 112

Now, we can divide (-105/960) by (15/112):
(-105/960) ÷ (15/112) = (-105/960) x (112/15) = (-105 x 112) / (960 x 15) = -11760 / 14400

To simplify this fraction further, we can find the greatest common divisor (GCD) of the numerator and the denominator, which is 240:
-11760/240 / 14400/240 = -49/60

Therefore, (-3/5)x(5/16)x(7/12) divided by (-3/16)x(-5/7) is equal to -49/60.
this is incorrect
Apologies for the mistake. Let's solve it correctly.

To solve the expression (-3/5) x (5/16) x (7/12) ÷ (-3/16) x (-5/7), we will use the properties of operations for multiplying and dividing fractions.

First, let's simplify each multiplication individually:
(-3/5) x (5/16) x (7/12) = (-3 x 5 x 7) / (5 x 16 x 12) = -105 / 960

(-3/16) x (-5/7) = (3 x 5) / (16 x 7) = 15 / 112

Now, let's divide -105/960 by 15/112:
(-105/960) ÷ (15/112) = (-105/960) x (112/15) = (-105 x 112) / (960 x 15) = -11760 / 14400

To simplify the fraction further, we can divide both the numerator and the denominator by their greatest common divisor (GCD), which is 240:
-11760/240 ÷ 14400/240 = -49/60

Therefore, (-3/5) x (5/16) x (7/12) ÷ (-3/16) x (-5/7) simplifies to -49/60.